Supervision Communication of the Regional Indonesian Broadcasting Commission (KPID) on Community Broadcasting Institutions (LPB) in West Sulawesi. - Urwa; Muhammad Anshar Akil; Ramsiah Tasruddin (Jurnal Mercusuar, 2022)
The main problem of this research is How is the Communication of KPID in Socialization and Supervision of Law No. 32 of 2002 in West Sulawesi? From this main problem, it is then divided into 2 sub-problems: 1. How is the communication process of KPID West Sulawesi in socializing Law Number 32 of 2002 regarding Subscription Television Institutions in West Sulawesi? and 2. How is the Communication of the Indonesian Regional Broadcasting Commission (KPID) in supervising Subscription Broadcasting Institutions in West Sulawesi? This research is qualitative in nature, in the form of field research. The approach used in this research is the Objective Communication and Subjective Communication approach. The data sources are primary data and secondary data, collected through observation, interviews, documentation, and supplemented with questionnaires as supporting data. Data processing and analysis techniques are conducted through data reduction, data presentation, and drawing conclusions. The research results show that in the supervision communication of KPID, several aspects are involved: internal control, formal control, informal control. The research also demonstrates that effective communication is required in interactions between parties, achieved through negotiation for agreements and understanding, while avoiding imposition or violence. Effective communication will establish humane relationships among them. KPID West Sulawesi should play a more assertive role, particularly in enforcing regulations, to align with the expectations of the Broadcasting Law No. 32 of 2002 and to ensure the functioning of the broadcasting system as desired by society. The regulation of the national broadcasting system is vital as it concerns the nation’s future. The strong influence of media on society cannot be denied, and negative consequences of media exposure must be promptly addressed